2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591592
|View full text |Cite
|
Sign up to set email alerts
|

Parallel generation of digitally reconstructed radiographs on heterogeneous multi-GPU workstations

Abstract: The growing importance of three-dimensional radiotherapy treatment has been associated with the active presence of advanced computational workflows that can simulate conventional x-ray films from computed tomography (CT) volumetric data to create digitally reconstructed radiographs (DRR). These simulated x-ray images are used to continuously verify the patient alignment in image-guided therapies with 2D-3D image registration. The present DRR rendering pipelines are quite limited to handle huge imaging stacks g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As was shown in Figure , although splatting was a simple and fast rendering algorithm using only a small subset of voxels, the images generated by ray‐casting have been smoother than those generated by splatting. A multi‐GPU workstation was applied for effective generations of DRRs. Comparative results of different registration methods (Table ) showed that: splatting was faster than ray‐casting; the GD algorithm was more effective than DS, with less consumption time; and the registration accuracy of MMI was the worst, resulting in the only two failures of the registration.…”
Section: Discussionmentioning
confidence: 99%
“…As was shown in Figure , although splatting was a simple and fast rendering algorithm using only a small subset of voxels, the images generated by ray‐casting have been smoother than those generated by splatting. A multi‐GPU workstation was applied for effective generations of DRRs. Comparative results of different registration methods (Table ) showed that: splatting was faster than ray‐casting; the GD algorithm was more effective than DS, with less consumption time; and the registration accuracy of MMI was the worst, resulting in the only two failures of the registration.…”
Section: Discussionmentioning
confidence: 99%
“…and are the input and output x-ray spectra respectively, as functions of photon energy expressed in electron volts, is the mass attenuation coefficient of the filtering material expressed in units cm 2 /g, is the density in units of g/cm 3 and is the thickness of the filtration in cm. Mass attenuation and density values were obtained from published tables [25].…”
Section: Wherementioning
confidence: 99%
“…An alternative to direct experimentation is the use of computer simulators. Existing techniques for the simulation of x-ray imaging systems have focussed primarily on Monte Carlo (MC) methods [1][2][3][4][5][6][7][8][9][10][11][12][13]. In general, these techniques are computationally expensive even when supported by graphical processing unit (GPU) acceleration [1][2][3][4][5][6][7] or when combined with deterministic calculations to speedup computation times [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation